Potensi Jus Buah Naga Merah (Hylocereus polyrhizus) terhadap Perbaikan Jaringan Organ Otak Tikus (Rattus norvegicus) Diabetes - Putra, I Gede Gelgel Bayu Surya; Simamora, Dorta (Universitas Wijaya Kusuma Surabaya, 2019)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia due to disturbances in insulin secretion, insulin action, or both. The purpose of this study was to analyze the effect of the red dragon fruit juice (Hylocereus polyrhizus) to repair brain organ histopathologic female wistar rats (Rattus norvegicus Wistar strain) with diabetes. This research is a true experiment research with randomized control - group pretest - posttest design and were conducted at the in Vivo Laboratory of Wijaya Kusuma University Surabaya. Twenty five female wistar rats were randomly divided into 5 groups, normal rats group KA (without alloxan induction), diabetic rats group KB (alloxan induction and without given any red dragon fruit juices), treatment group KC (alloxan induction + 2 gr/2,5ml of red dragon fruit juices), treatment group KD (alloxan induction + 4 gr/2,5ml of red dragon fruit juices) and treatment group KE (alloxan induction + 8 gr/2,5ml of red dragon fruit juices). The study was conducted during the period of 16 days with standard feeding adaptations for 7 days. On day 16, all the rats were terminated. Glucose meter is used to measure the levels of blood glucose in rats. Histopathologic observation of rat brain tissue using a microscope Olympus CX21 with Haematoksilin eosin (HE) staining. The results showed the best dose of red dragon fruit juices to decrease blood glucose levels compare between KB and KE with significance p-value = 0.000 (? < 0.05), the blood glucose levels decreased in diabetic rats significantly between KB and KE also decreased in rat brain tissue necrosis with p-value = 0.000 (? <0.05).